Influence of NOS1 on verbal intelligence and working memory in both patients with schizophrenia and healthy control subjects. - DONOHOE, GARY; MORRIS, DEREK; CORVIN, AIDEN; O'DONOGHUE, THERESE; GILL, MICHAEL; QUINN, EMMA (My University, 2009)
Background: Human and animal studies have implicated the gene NOS1 in both cognition and schizophrenia susceptibility. Objectives: To investigate whether a potential schizophrenia risk SNP (rs6490121) identified in a recent genome-wide association study (O?Donovan et al., PMID 18677311) negatively influences cognition in patients with schizophrenia and healthy controls. Design: A comparison of both cases and controls grouped according to NOS1 genotype (GG v AG v AA) on selected measures of cognition in two independent samples. Setting: Unrelated patients from general adult psychiatric inpatient and outpatient services and unrelated healthy volunteers from the general population were ascertained. Participants: Patients with DSM-IV diagnosed schizophrenia and healthy controls from independent samples of Irish (n=349 cases and n=230 controls) and German (n=232 cases and n=1344 controls) nationality. Method: We tested for association between NOS1 rs6490121 and cognitive functions known to be impaired in schizophrenia (IQ, episodic memory, working memory, and attentional control) in the Irish sample. We then sought to replicate significant results in the German sample. Results: A main effect of NOS1 genotype on verbal IQ and working memory was observed in Irish samples where the homozygous carriers of the schizophrenia risk `G? risk allele performed poorly compared with the other genotype groups. These findings replicated in the German sample, again with the GG genotype carriers performing below other genotype groups. Post-hoc Analysis of additional IQ measures (Full scale and Performance IQ) in the German sample revealed that NOS1 GG carriers underperformed on these measures also. Discussion: NOS1 is associated with clinically significant variation in cognitive. Whether this is a mechanism by which SZ risk is increased (e.g. via an influence on cognitive reserve) is yet to be confirmed.
PUBLISHED
Keywords: Cognition; Genetics; Genes & Society; Neuroscience